Political Dynamics of Cybersecurity Policy in Indonesia: A Governmentality Analysis under Joko Widodo’s Administration (2014-2024) - Anggi Anggraeni Kusumoningtyas; Syarkawi Syarkawi (Journal of Contemporary Local Politics, 2025)
This article examines Indonesia’s cybersecurity policy during the Joko Widodo administration (2014–2024) through the lens of Michel Foucault’s concept of governmentality. As cyberspace has increasingly been constructed as a strategic domain of governance, the Indonesian state has framed cyber threats as risks to national security, digital sovereignty, and political stability. This framing has justified the expansion of regulatory authority, institutional consolidation, and digital surveillance practices. Using a qualitative document analysis approach, this study analyzes cybersecurity-related laws, presidential regulations, national cybersecurity strategies, and official reports issued by state institutions, particularly the National Cyber and Crypto Agency. The findings demonstrate that cybersecurity policy in Indonesia functions not merely as a technical mechanism to protect digital infrastructure, but also as a political technology of governance. Through the production of threat discourses, the deployment of governing technologies, and the shaping of digital subjectivities, cybersecurity policy operates as a form of population management that encourages self-regulation and compliance among citizens. Drawing on governmentality theory, this article argues that cybersecurity governance reflects broader state strategies to regulate conduct in the digital sphere rather than simply respond to technical risks. The study contributes to debates on digital governance and local politics by highlighting how cybersecurity policy in a democratic developing country simultaneously enhances state capacity while generating tensions with democratic accountability, civil liberties, and digital rights.